Prothrombin Time (PT), Activated Partial Thromboplastin Time (APTT), Fibrinogen, and D-dimer in Coronavirus Disease 2019 Outcome - Atmaja, Fredy Wirya; Adiyanti, Sri Suryo; Kristanty, Diyah; Dwira, Surya; Kusmardi, Kusmardi (Indonesian Journal of Medical Chemistry and Bioinformatics, 2024)
COVID-19, caused by SARS-CoV-2 has been reported to be associated with coagulopathy and DIC. This study aimed to investigate the profiles and differences of PT, APTT, fibrinogen, and D-dimer in COVID- 19 outcome. This retrospective cohort was conducted at Central Laboratory Clinical Pathology Department of dr. Cipto Mangunkusumo Hospital from July – December 2020. Demographic, clinical, and laboratory data were extracted from EHR and compared between poor and good outcome. Ninety-seven subjects were confirmed positive COVID-19, 45 of whom (46.4%) were in poor outcome group, while 52 subjects (53.6%) were in good outcome group. Median of PT 11.0” (9.7-28.3), APTT 38.4” (23.9-121), fibrinogen 484.8 mg/dL (51.2-940.9), and D-dimer 1,800 µg/L (190-35,200). Longer PT, APTT, and higher D-dimer (p < 0.05), while lower fibrinogen (p > 0.05) was found in poor outcome group. There were significant differences of PT, APTT and D-dimer in COVID-19 outcome.